1998
DOI: 10.1046/j.1523-1755.1998.00946.x
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin converting enzyme gene I/D polymorphism in essential hypertension and nephroangiosclerosis

Abstract: An insertion/deletion (I/D) polymorphism of the angiotensin converting enzyme (ACE) gene significantly influences circulating ACE levels and plays a role in the development of target organ damage, that is, left ventricular hypertrophy in essential hypertension (EH), and microalbuminuria in diabetes mellitus. We have examined the role of the I/D polymorphism in essential hypertensive patients with renal involvement. The study was divided in two independent protocols. In protocol 1, we retrospectively analyzed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
43
1
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 24 publications
3
43
1
3
Order By: Relevance
“…Another recent review counted 12 positive and 14 'negative' publications on this issue (Agarwal et al 2005). Likewise, available evidence suggest that the D allele causes a modest-and most likely irrelevant-increase in the risk for other cardiovascular and renal diseases (Cambien et al 1992;Schunkert et al 1994;Iwai et al 1994;Pontremoli et al 1996;Fernandez-Llama et al 1998). For these entities, meta-analyses revealed odds ratios for carriers of the DD genotype ranging from 1.04-1.43 for myocardial infarction (Agerholm-Larsen et al 2000;Keavney et al 2000) and from 1.28-1.56 (Staessen et al 1997;Ng et al 2005) for diabetic nephropathy.…”
Section: Polymorphisms In the Angiotensin Converting Enzymementioning
confidence: 99%
“…Another recent review counted 12 positive and 14 'negative' publications on this issue (Agarwal et al 2005). Likewise, available evidence suggest that the D allele causes a modest-and most likely irrelevant-increase in the risk for other cardiovascular and renal diseases (Cambien et al 1992;Schunkert et al 1994;Iwai et al 1994;Pontremoli et al 1996;Fernandez-Llama et al 1998). For these entities, meta-analyses revealed odds ratios for carriers of the DD genotype ranging from 1.04-1.43 for myocardial infarction (Agerholm-Larsen et al 2000;Keavney et al 2000) and from 1.28-1.56 (Staessen et al 1997;Ng et al 2005) for diabetic nephropathy.…”
Section: Polymorphisms In the Angiotensin Converting Enzymementioning
confidence: 99%
“…13 Subjects were classified as II, DD or heterozygote for insertion/deletion (DI). Mistyping of DI heterozygotes as DD due to preferential amplification of the D allele and inefficiency in amplification of the I allele has been described.…”
Section: Determination Of Ace Genotypementioning
confidence: 99%
“…15,16 Crosssectional association studies, meanwhile, have reported a lack of impact of the polymorphisms of the AGT gene on microalbuminuria. [17][18][19] Observing the changes in microalbuminuria during antihypertensive treatment in patients carrying different alleles of the polymorphisms is another potential approach to studying whether or not polymorphisms of the AGT gene influence microalbuminuria. In the present study, the influence of the A-6G polymorphisms of the AGT gene on the outcome of microalbuminuria during a 3-year antihypertensive treatment was analysed in a group of young adults with essential hypertension, never previously treated with antihypertensive drugs.…”
Section: Introductionmentioning
confidence: 99%